Urbanizaciones de origen informal en Buenos Aires. Lógicas de producción de suelo urbano y acceso a la vivienda - Di Virgilio, María Mercedes (El Colegio de México A.C., 2015)
Since its inception, the Metropolitan Area of Buenos Aires (AMBA) has seen the coexistence of multiple modes of urban informality. This paper analyzes the production and processing of the forms of informal habitat that develop on vacant land in the AMBA. The results presented are part of a research project exploring the transformations of four popular AMBA developments from their inception to the present, using quantitative and qualitative techniques. The article engages in a dialogue with research that explores the everyday life of the popular sectors and forms of housing access in recent decades.